Associations between patient factors and adverse events in the home care setting: a secondary data analysis of two canadian adverse event studies - Nancy A. Sears; Régis Blais; Michael Spinks; Michèle Paré; G. Ross Baker (BMC, 2017)
Abstract Background Early identification of patients at who have a higher risk for the occurrence of harm can provide patient safety improvement opportunities. Patient factors contribute to adverse event occurrence. The study aim was to identify a single, parsimonious model of home care patient factors that, regardless of location and differences in home care program management and design factors, could provide a means of locating patients at higher and lower risk of harm. Methods Split modeling using secondary analyses of data from two recent Canadian home care patient safety studies was undertaken. Patient factors from the Minimum Data Set Resident Assessment Instrument (RAI) for Home Care and diagnoses consistent with ICD-10 and RAI-Mental Health assessment were used. Continuous and categorical measures of factors were considered. Adverse events were defined using World Health Organization taxonomy and measured on a dichotomous yes/no scale. Patient factors significantly associated (Pearson's Chi Square, p ≤ .05) with the occurrence of adverse events in both earlier studies were entered in forward selection regression analyses to locate factors predictive of adverse event occurrence. Results Instrumental activities of daily living dependency and escalating co-morbidity counts are associated with patient vulnerability to adverse events. Conclusions Instrumental activities of daily living dependency and burden of illness, both easily identifiable early in the episode of care, are significantly associated with the risk of adverse event occurrence, however there is regional variability in the relationships.